Скоростная типизация средней и нижней мантии Европы - Бугаенко, И.В.; Заец, Л.Н.; Цветкова, Т.А. (Геофизический журнал, 2015)
У роботі використано 3D Р-швидкісну модель мантії Європи. Модель побудовано за запропонованим В.С. Гейком методом тейлорового наближення розв'язку задачі сейсмічної томографії. Проведено аналіз швидкісної будови середньої та нижньої мантії цієї швидкісної моделі. Під Європою виділено чотири типи мантії: стабільна, активізована, усталена за активізованим типом, не усталена за стабільним типом. We used 3D Р-velocity model of the mantle of Europe. The model was constructed by V.S. Geyko's proposed method of Teylor approximate solution of seismic tomography. The velocity structure of the middle and lower mantle of the velocity model was analyzed. Four types of mantle have been allocated under Europe: the stable mantle, the activated mantle, the mantle unsteady on an activated type, the unsteady mantle on a stable type.